2018
DOI: 10.1002/stc.2281
|View full text |Cite
|
Sign up to set email alerts
|

Localization and quantification of partial cable damage in the long-span cable-stayed bridge using the abnormal variation of temperature-induced girder deflection

Abstract: The cable damage is one serious problem to endanger the bridge safety. Considering that current methods of estimating cable damage still have some shortcomings during their application, this paper introduced one new method to localize and quantify the partial cable damage using the abnormal variation of temperature-induced girder deflection caused by cable damage. First, the monitoring correlation between girder deflection and uniform temperature is analyzed using the monitoring temperature and deflection data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Luo used 268 vibrating wire sensors, which integrate the test functions of stress and temperature, to measure the temperature and stress of the Beijing National Stadium's space truss structure in order to directly study the correlation between temperature field and stress, and the test results showed that the variation of temperature field was an important factor leading to high stress [30]. To study the relationship between the temperature field and the deflection of the steel box girder in the Zhijiang Cable-Stayed Bridge, 14 temperature sensors and 18 deflection sensors were arranged along the longitudinal direction of the bridge, with the longitudinal positions of T1-T14 and D3-D16 being the same [134]; the specific positions of these temperature and deflection sensors are shown in Figure 7. Based on comparative analysis of the test data, it was shown that the time-variance laws of girder temperature and girder deflection were similar, and there was a basically linear relationship between the temperature field and the deflection of the box girder at night, indicating that the girder deflection was greatly affected by the girder temperature.…”
Section: Experimental Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo used 268 vibrating wire sensors, which integrate the test functions of stress and temperature, to measure the temperature and stress of the Beijing National Stadium's space truss structure in order to directly study the correlation between temperature field and stress, and the test results showed that the variation of temperature field was an important factor leading to high stress [30]. To study the relationship between the temperature field and the deflection of the steel box girder in the Zhijiang Cable-Stayed Bridge, 14 temperature sensors and 18 deflection sensors were arranged along the longitudinal direction of the bridge, with the longitudinal positions of T1-T14 and D3-D16 being the same [134]; the specific positions of these temperature and deflection sensors are shown in Figure 7. Based on comparative analysis of the test data, it was shown that the time-variance laws of girder temperature and girder deflection were similar, and there was a basically linear relationship between the temperature field and the deflection of the box girder at night, indicating that the girder deflection was greatly affected by the girder temperature.…”
Section: Experimental Testmentioning
confidence: 99%
“…Many studies [36,73,134] have shown that non-uniform temperature-induced effects have a significant adverse effect on the performance of steel structures, but few studies have referred to a method for reducing these adverse effects. The application of radiation-proof paint effectively reduces the ability of steel structures to absorb solar radiation energy, or enhance the convective effect by strengthening the air flow at the steel structure's surface, then lowering the structural temperature and weakening the temperature effect.…”
Section: Other Aspectsmentioning
confidence: 99%
“…Stay cables are the main force-bearing structures of cable-stayed bridges, [1][2][3] and they are mainly composed of internal high-strength steel wires and external high-density polyethylene (HDPE) sheaths. 4 However, HDPE sheaths may be cracked or damaged for various reasons, 5 leading to corrosion of steel wires at the cracked part of the sheaths. 6,7 The impressed current cathodic protection (ICCP) technique is widely employed in the corrosion protection of marine ships, 8 reinforced concrete, 9 and buried pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…Bridge expansion joints are designed to accommodate expansion and contraction of the bridge resulting from a variety of factors such as thermal effect, concrete shrinkage, creep, live loading, settlement of the foundation and substructure, and environmental variations . Effective functioning of expansion joints is required not only for smooth traffic but also for ensuring bridge performance in extreme events, such as earthquakes and hurricanes.…”
Section: Introductionmentioning
confidence: 99%